Graphene-like metal–organic frameworks: morphology control, optimization of thin film electrical conductivity and fast sensing applications. Issue 41 (27th September 2018) - Hoppe, Bastian; Hindricks, Karen D. J.; Warwas, Dawid P.; Schulze, Hendrik A.; Mohmeyer, Alexander; Pinkvos, Tim J.; Zailskas, Saskia; Krey, Marc R.; Belke, Christopher; König, Sandra; Fröba, Michael; Haug, Rolf J.; et al.
Abstract : Platelets of the Cu3 hhtp 2 -MOF are used for coatings and sensing. Abstract : The metal–organic framework Cu-2, 3, 6, 7, 10, 11-hexahydroxytriphenylene (Cu3 hhtp 2 -MOF), a copper-based graphene-like framework, is one of the few MOFs featuring inherent electrical conductivity. Here, we investigate the synthesis of this material with regard to the influence of different additives. It is shown that ammonia acts as a modulator leading to platelet-like particles in a water-based synthesis system. This material is thoroughly characterized by X-ray diffraction (XRD), electron microscopy, atomic force microscopy (AFM), physisorption, thermal behaviour, and electrical conductivity. The measured conductivity value of 0.045 S cm −1 surpasses all formerly reported measurements. The obtained platelets appear especially suitable for the preparation of different devices. As an example, we prepared thin and homogenous films by spray-coating water-based dispersions of this MOF on glass and on polymer substrates. In the films, the platelets are oriented parallel to the substrate and are in intimate contact. This leads to a high electrical conductivity combined with an easily accessible pore system. The applicability of such coatings is shown in a preliminary sensing test, showing quick and strong response and fast recovery. This work shows that control of the crystal morphology combined with suitable preparation procedures can enhance the performance of MOF-based devices.